The effects of the combination of angiotensin-converting enzyme inhibitor and diuretic on the lower limb venous circulation in men with hypertension and chronic venous disorders - S. V. Letyagina; V. M. Baev; S. A. Shmeleva; T. Yu. Agafonova (Российский кардиологический журнал, 2020)
Aim. To study the effects of angiotensin converting enzyme (ACE) inhibitor and diuretic combination on the lower limb venous circulation in men with hypertension (HTN) and chronic venous disorders (CVD).Material and methods. The study included 37 men with uncontrolled hypertension at the age of 46 (40-49) years, which were divided into two groups: 20 patients with objective signs of CVD (CEAP criteria) and 17 patients without CVD. During hospitalization, all participants received antihypertensive therapy with a combination of ACE inhibitor and diuretic. Vein Doppler ultrasound at rest was performed on the day of hospitalization and after 14 days. The diameter and the area of vein lumen, flow velocity and peripheral venous pressure (PVP) were recorded. Mann-Whitney and Wilcoxon tests were used for statistical analysis.Results. Initially, patients with CVD had higher values of PBP (by 26%), diameter and area of the vein lumen (53%) and flow velocity (by 14%) than in patients without CVD. As a result of therapy, in the group of patients with HTN and without CVD, systolic (SBP) and diastolic blood pressure (DBP) decreased to the target levels, PVP decreased by 13%, vein diameter increased by 27%, blood flow velocity decreased by 15%. Therapy in patients with CVD led to the normalization of SBP, DBP, and a decrease in PVP and flow velocity by 31% and 33%, respectively. No significant changes in the diameter and cross-sectional area of lower limb veins were noted.Conclusion. The obtained data showed that 14-day antihypertensive therapy with ACE inhibitor and diuretic in patients with HTN and CVD, unlike patients with HTN and without CVD, did not led to vein dilation, but was associated with flow velocity and PVP decrease. By therapy’s end, most of venous hemodynamic parameters, including PVP, were identical in the studied groups.